The Use of Satirical Language Style Markers in Gus Mus’s Poetry Collection - Imran, Reski Wahyuni; Anzar, Anzar; Yusuf, Akram Budiman (Gema Wiralodra, 2025)
This study aims to describe the use of satirical language markers in the form of irony, cynicism, and sarcasm in Gus Mus’s poetry collection. The research employs a qualitative descriptive method based on Gorys Keraf’s stylistic theory. The data consist of poetry excerpts analyzed to reveal the function of satire in exposing the hypocrisy of power, social alienation, and moral degradation in society. The findings show that irony is used to uncover identity crises and structural injustice, cynicism to criticize the decline of values and socio-religious hypocrisy, and sarcasm to mock double standards and political manipulation. These findings affirm that satirical language in Gus Mus’s poetry functions as a strategy of social criticism and a means of fostering critical awareness among the people.